2014
DOI: 10.1177/1350507614529512
|View full text |Cite
|
Sign up to set email alerts
|

Exploring managerial talk through metaphor: An opportunity to bridge rigour and relevance?

Abstract: In this article, we elucidate that exploring managerial talk through the lens of metaphor might offer an opportunity to bridge the often acclaimed gap between rigour and relevance in management research and education. Building on an interpretative research approach and a qualitative field study among managers from the Netherlands, Poland and the United States, we reveal that managers view their day-to-day interactions in relationships with suppliers and clients as if they perform acts, play games and fight bat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 76 publications
0
16
0
1
Order By: Relevance
“…Put differently, respondents are invited to participate in the poetic construction as well as displacement of metaphors (Cunliffe, 2002) as visitors in a carnival are invited to join the festivities. For example, in a recent study (Latusek and Vlaar, 2015), the authors suggest that while the three metaphors they found seemed to dominate the narratives of managers as to how they understand their day-to-day activities, they are also mindful that this might be a reflection of their methodology and irrational commitment to the metaphors employed. Using the framework developed here, the authors might have invited their respondents to reflect on this and indeed focused further on their participants' "micro-level" (Latusek and Vlaar, 2015: 226) behavior by asking them to play with instances when the metaphors were undermined rather than supported.…”
Section: Resultsmentioning
confidence: 99%
“…Put differently, respondents are invited to participate in the poetic construction as well as displacement of metaphors (Cunliffe, 2002) as visitors in a carnival are invited to join the festivities. For example, in a recent study (Latusek and Vlaar, 2015), the authors suggest that while the three metaphors they found seemed to dominate the narratives of managers as to how they understand their day-to-day activities, they are also mindful that this might be a reflection of their methodology and irrational commitment to the metaphors employed. Using the framework developed here, the authors might have invited their respondents to reflect on this and indeed focused further on their participants' "micro-level" (Latusek and Vlaar, 2015: 226) behavior by asking them to play with instances when the metaphors were undermined rather than supported.…”
Section: Resultsmentioning
confidence: 99%
“…A qualitative research approach was adopted, using the case study methodology, as its strong link between education and research is widely recognized (Lamy & Lapoule, 2012;Latusek & Vlaar, 2014). This supports the increasing encouragement of combining teaching and research in management teaching and research institutions (Gill, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Entrepreneurial narratives are embodied in metaphors (Duncan & Pelly, 2016). Metaphors are powerful tools for sense-making, sense-giving and the development of theory (Latusek & Vlaar, 2015). Metaphors emphasize a particular aspect of what we want to describe and downplay other aspects, those which do not fit the metaphor (Jackson & Carter, 2007).…”
Section: Costumes and Makeupmentioning
confidence: 99%